Letter (copy) - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
C02-0005-001 Deveney 2nd December, 1940. Lieut. George Jeger, R.A.P.C. Wood Hall, Lower Park Road. Victoria Park, MANCHESTER, 14. Dear Jeger, Just a brief note immediately on my safe return to London to thank you for your hospitality in Manchester and to say how glad I was to see you in such a good form in the dreadful circumstances of the War. It is fine to talk over things. I have bought a new hat ( Austin Reed ) and I am forwarding the Bill to the Grand Hotel. I got into Bletchley at 8 a.m. on Sunday — a slow tedious journey. I am enclosing a reply re Sergeant P.J. Deveney. You will see they want a query answered. Ask him to deal with it at once and to let me know. I am enclosing a resolution for the Trustees' signature as approved re the guarantee for the Trade Union Club. I informed Peacock to-day of your agreement and he was pleased. Again many thanks. Yours sincerely, Letter - Original. Resolution. 292C/946/2/5